Карбоксиметилированный химический реагент для буровых промывочных жидкостей - Базарнова Н. Г.; Галочкин А. И.; Маркин В. И.; Токарева И. В.; Горулев О. А.; Блонский А. Г.; Чубик П. С. Петр Савельевич; Годунов Е. Б.
опубл. 10.03.99